Controlling the Assembly of Coiled–Coil Peptide Nanotubes. (14th December 2015) - Thomas, Franziska; Burgess, Natasha C.; Thomson, Andrew R.; Woolfson, Derek N.
Abstract: An ability to control the assembly of peptide nanotubes (PNTs) would provide biomaterials for applications in nanotechnology and synthetic biology. Recently, we presented a modular design for PNTs using α‐helical barrels with tunable internal cavities as building blocks. These first‐generation designs thicken beyond single PNTs. Herein we describe strategies for controlling this lateral association, and also for the longitudinal assembly. We show that PNT thickening is pH sensitive, and can be reversed under acidic conditions. Based on this, repulsive charge interactions are engineered into the building blocks leading to the assembly of single PNTs at neutral pH. The building blocks are modified further to produce covalently linked PNTs via native chemical ligation, rendering ca. 100 nm‐long nanotubes. Finally, we show that small molecules can be sequestered within the interior lumens of single PNTs.